Determining Accessibility to Tourist Attractions - Al Kahtani, S.; Xia, Jianhong (Cecilia); Veenendaal, Bert (School of Mathematical and Geospatial Sciences RMIT University, 2013)
Accessibility to tourist attractions is fundamental to the effective utilisation of tourist sources. This paper outlines methods developed to measure accessibility to tourist attractions. Accessibility indexes were developed as a quantitative measure of accessibility. The three accessibility indices developed are based on tourist attraction functionalities, attraction facilities, and the quality of road networks that provide access to them. The normalised weighted method was used to extract accessibility indexes from tourist attraction functionalities and facilities, and the quality of road networks. Factor analysis was used to reorganise the variables of facilities and functionalities into new accessibility factors. These provide a means of identifying and combining similar variables into new factors to facilitate the understanding of the nature of accessibility (or lack of it) to the attractions. This study was applied in Ningaloo Coast Region, Western Australia. The results are used to assist decision makers to decide how to improve accessibility to tourist attractions.